A comparison of the use of video and audio media in English vocabulary acquisition / Pungodi Shanmugam - Pungodi , Shanmugam (2018)
Video has been applied as a tool in designing Instruction to optimize Second Language Acquisition (SLA). Little research has been done on the effects of this tool on English language learning especially in the context of vocabulary instruction. The current empirical study attempts to investigate the use of video and audio in vocabulary acquisition. Video has significant effects on vocabulary learning among students. In this quantitative and qualitative study, data is gathered using a pretest-posttest and delayed post-test design. Specifically, the participants of 20 students from a school in Port Dickson would be assigned into two groups to administer the video and audio vocabulary acquisition. The pre and post activities related to the British Animated Video require participants answering VKS test and fill-in-the -blanks. The improvement on students` vocabulary knowledge is determined by analyzing the score obtained. This study helps to investigate the use of video and audio for vocabulary acquisition and contribute to the body of knowledge on vocabulary teaching instruction. This study has shown that students can acquire vocabulary through audio and video. However, most of the students prefer video then audio because it illustrates visual examples to help develop understanding in vocabulary acquisition.